Analisis Program Pemberian Makanan Tambahan (PMT) Pada Status Gizi Balita di Kelurahan Rappang Sidenreng Rappang - Hastina, Hastina; Mardhatillah, Mardhatillah; Adri, Khaeriyah; Febrianti, Devy (Jurnal Administrasi Politik dan Sosial, 2024)
Providing Supplementary Food (PMT) is one way to meet the nutritional needs of toddlers. This program requires collaborative action from all parties, but there are still problems in the input, processing and output processes so that the distribution process is not yet good. This research aims to find out how the input, process and output are carried out well. This research uses quantitative methods with a cross sectional approach, using cluster random sampling. The data collection techniques used in this research are observation, interviews, population and questionnaires. As well as data analysis techniques in this research using validity tests, reliability tests, and chi-square tests. The results of this research show that financing with a p value of 0.018 (p < 0.005) and implementation of the PMT program with a p value of 0.007 (p < 0.005) show a significant relationship to the nutritional status of toddlers in Rappang Village and Human Resources (SDM) with a value of p amounting to 0.104 (p > 0.005) which shows there is no significant relationship with the nutritional status of children under five in Rappang Village.